SUSTAINABILITY AND FIRM PERFORMANCE: EMPIRICAL STUDY ON IDX ESG LEADERS - Zuraida; Muhammad Ihsan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to assess the relationship between sustainability disclosure and firm performance among companies listed on the Indonesia Stock Exchange (IDX) ESG Leaders Index during the years 2020 to 2022. The study sample included 54 observations from 18 companies listed on the IDX ESG Leaders Index between 2020 and 2022. Data were gathered from sustainability reports, annual reports, and publicly accessible capital market data. Analysis was conducted using multiple linear regression in Stata IC 15. The link between sustainability disclosure and financial performance is as follows: social factors positively impact financial performance, measured by ROA, while environmental and economic factors have a negative influence. Governance factors, however, do not significantly impact firm performance. Additionally, the link between financial factors and financial performance is as follows: size negatively influence performance, while age and leverage positively impact it. The study's scope is limited to ESG Leaders, comprising only 18 companies, and investigates a three-year period from 2020 to 2022. Therefore, the observations are constrained by this limited sample size and timeframe. The significance of this research lies in its focus on IDX ESG Leaders Companies, and the nuanced examination of the relationships between sustainability factors and financial performance. By exploring these links in a distinctive setting and presenting findings that contrast with broader trends, the study contributes valuable insights for policymakers.